Emergency physician use of end‐tidal oxygen monitoring for rapidsequence intubation - Matthew Oliver; Nicholas D. Caputo; Jason R. West; Robert Hackett; John C. Sakles (Journal of the American College of Emergency Physicians Open)
Abstract Background End‐tidal oxygen (ETO2) monitoring is used by anesthesiologists to quantify the efficacy of preoxygenation before intubation but is generally not used in emergency departments (EDs). We have previously published our findings describing preoxygenation practices in the ED during blinded use of ETO2. The purpose of this investigation is to determine whether the unblinded use of ETO2 monitoring led to improvements in preoxygenation during rapid sequence intubation in the ED and also the oxygen device or technique changes that were used to achieve higher ETO2 levels. Methods We conducted an interventional study at 2 academic EDs in Sydney, Australia and New York City, New York using ETO2 monitoring to investigate the preoxygenation process and effectiveness. We used data collected during a previous descriptive study for the control group, in which care teams in the same 2 EDs were blinded to the ETO2 value. In the study group, clinicians could utilize ETO2 to improve preoxygenation. Following an education process, clinicians were able to choose the method of preoxygenation and the techniques required to attempt to achieve an ETO2 level >85%. The primary outcome was the difference in ETO2 levels at the time of induction between the control and study group and the secondary outcome included the methods that were attempted to improve preoxygenation. Results A convenience sample of 100 patients was enrolled in each group. The median ETO2 level achieved at the time of induction was 80% (interquartile range 61 to 86, overall range 73) in the control group and 90% in the study group (interquartile range 83 to 92, overall range 41); the median difference was 12 (95% confidence interval: 8, 16, P = < 0.001). The majority of oxygen device changes were from non‐rebreather mask to bag‐valve‐mask (BVM) (15%, n = 15) and changes in technique from improvements in mask seal (54%, n = 34). The final device used in the study group was BVM in 87% of cases. Conclusions In 2 clinical studies of ETO2 in academic EDs, we have demonstrated that the use of ETO2 is feasible and associated with specific and potentially improved approaches to preoxygenation. A clinical trial is needed to further study the impact of ETO2 on the preoxygenation process and the rate of hypoxemia.